The Claustrum and Insula in Microcebus murinus: A High Resolution Diffusion Imaging Study - Park, Soyoung; Tyszka, Mike; Allman, John M. (Frontiers in Neuroanatomy, 2012)
The claustrum and the insula are closely juxtaposed in the brain of the prosimian primate, the gray mouse lemur (Microcebus murinus). Whether the claustrum has closer affinities with the cortex or the striatum has been debated for many decades. Our observation of histological sections from primate brains and genomic data in the mouse suggest former. Given this, the present study compares the connections of the two structures in Microcebus using high angular resolution diffusion imaging (HARDI, with 72 directions), with a very small voxel size (90 micra), and probabilistic fiber tractography. High angular and spatial resolution diffusion imaging is non-destructive, requires no surgical interventions, and the connection of each and every voxel can be mapped, whereas in conventional tract tracer studies only a few specific injection sites can be assayed. Our data indicate that despite the high genetic and spatial affinities between the two structures, their connectivity patterns are very different. The claustrum connects with many cortical areas and the olfactory bulb; its strongest probabilistic connections are with the entorhinal cortex, suggesting that the claustrum may have a role in spatial memory and navigation. By contrast, the insula connects with many subcortical areas, including the brainstem and thalamic structures involved in taste and visceral feelings. Overall, the connections of the Microcebus claustrum and insula are similar to those of the rodents, cat, macaque, and human, validating our results. The insula in the Microcebus connects with the dorsolateral frontal cortex in contrast to the mouse insula, which has stronger connections with the ventromedial frontal lobe, yet this is consistent with the dorsolateral expansion of the frontal cortex in primates. In addition to revealing the connectivity patterns of the Microcebus brain, our study demonstrates that HARDI, at high resolutions, can be a valuable tool for mapping fiber pathways for multiple sites in fixed brains in rare and difficult-to-obtain species.